(untitled) (Universal International Scientific Journal, 2026)
This article examines the work of many local and foreign scientists and reflects their ideas and observations on the development of thinking, which is currently underway in our country to improve the scientific, methodological and organizational foundations of improving the professional knowledge, practical skills, and professional qualifications of physical education and sports specialists.